Application of local biomass as an adsorbent for removal of phenol from aquoeus solution - Nurul Ilyana, Ali (2010)
This paper shows a detailed study to observe the efficiency of banana peel and orange peel as a low cost adsorbent to remove phenol from aqueous solution.The banana and orange peel were used as biomass and obtained locally.The biomass initially was pre-treat into small particle and dried at 60oC for 48 hours.There were three parameters studied in this paper which was the effect of adsorption time,effect of adsorbent dosage and effect of pH.From the experiment,it was found that the optimum adsorption time for banana peel as adsorbent was 240 minutes which equal to 4 hours;the optimum adsorbent dosage was 0.5g based on the higher adsorption capacity per unit mass of adsorbent and the optimum pH was in basic condition with pH 9 to 11.At this optimum condition,the phenol uptake was increase.As for orange peel, the maximum percentage of phenol removal was 24% at condition of initial concentration was 100mg/L;adsorption time was 240 minutes;adsorbent dosage was 0.5g and pH of solution is 11.The phenol uptake was analyzed using UV-Visible spectrophotometer.From the result,it was proven that banana peel and orange peel can be one type of low cost adsorbent but it also shows that banana peel was better in phenol removal compared to orange peel and this method can be applied in industrial wastewater.